Implanting Vocabulary for Long Terms Memory through Memrise and Quizlet Applications - Fadhilawati, Dian; Ulum, Bahrul; Rachmawati, Dwita Laksmita (Lembaga Penelitian dan Pengabdian kepada Masyarakat, 2022)
The student's ability in understanding and using academic and research vocabulary was lack. Therefore, this research tries to enhance the studentsâ€™ vocabulary achievement by applying Memrise and Quizlet Applications at one of the private university in east Java, Indonesia. This research applied Classroom Action Research using four procedures: Planning, Acting, Observing, and Reflecting. The researchers obtained the data from tests and questionnaires. The result reveals that the vocabulary implantation through Â Memrise and Quizlet applications increases the students' achievement from the average score of 55.62 in Pre-Test to 89.54 in Post-Test. Furthermore, the students also presented a positive attitude (91%) to the implementation of Memrise and Quizlet for learning vocabulary. The lecturers or teachers can use Memrise and Quizlet Applications as media to motivate students and provide them with fun and independent learning. The students' vocabulary achievement increased after learning vocabulary using Memrise and Quizlet applications from the result presented above. The majority of the participants in this research also favored using Memrise and Quizlet applications to implant the vocabulary. Therefore, the researchers suggest that the teachers or lecturers who teach vocabulary use Memrise and Quizlet applications as an alternative media to implant the vocabulary materials to the students in long-term memory.